Design Approach to Building a Research and Development Laboratory for Testing Industrial Fans and Other Equipment - Piwowarski, Marian; Ziemiański, Paweł; Mioduszewski, Piotr; Czyżewicz, Jacek; Jaskólski, Piotr; Bortkiewicz, Mateusz; Laszuk, Krzysztof; Madej, Krzysztof; Kopaczewski, Krzysztof; Cybulski, Karol; Naumczyk, Tomasz; Fabiański, Tomasz; et al. (Instal, 2025)
Industrial fans are among the largest standalone consumers of mechanical drive energy in various sectors. As such, they represent a key area for energy savings aimed at reducing CO2 emissions. The ubiquity of fans and their frequent operation under non-optimal conditions present an opportunity for substantial global reductions in the energy used to power them. In addition to energy efficiency, noise generated by fans constitutes another important concern. This article presents the process of designing and testing of a modern research laboratory dedicated to measurements and analysis of fan performance parameters. The project was implemented as part of an innovative research and development initiative under the COLUBRIS project carried out by the Nyborg-Mawent company. The article provides detailed information on the laboratory’s structure, functional layout, applied technical solutions, and measurement equipment, which enables the collection of reliable data related to both energy efficiency and noise emission. Thanks to its flexible structure and advanced equipment, the laboratory enables a controlled flow, acoustic, and vibration testing not only of fans but also of other types of devices under various environmental conditions. The paper presents also preliminary results of energy and noise measurements conducted on fans in this laboratory. These findings serve as an important starting point for the technological development of equipment aimed at improving efficiency while minimizing negative environmental impact and user exposure.